Clark’s Nutcrackers (Nucifraga columbiana) Flexibly Adapt Caching Behavior to a Cooperative Context - Clary, Dawson; Kelly, Debbie M. (Frontiers in Psychology, 2016)
Corvids recognize when their caches are at risk of being stolen by others and have developed strategies to protect these caches from pilferage. For instance, Clark’s nutcrackers will suppress the number of caches they make if being observed by a potential thief. However, cache protection has most often been studied using competitive contexts, so it is unclear whether corvids can adjust their caching in beneficial ways to accommodate non-competitive situations. Therefore, we examined whether Clark’s nutcrackers, a non-social corvid, would flexibly adapt their caching behaviours to a cooperative context. To do so, birds were given a caching task during which caches made by one individual were reciprocally exchanged for the caches of a partner bird over repeated trials. In this scenario, if caching behaviours can be flexibly deployed, then the birds should recognize the cooperative nature of the task and maintain or increase caching levels over time. However, if cache protection strategies are applied independent of social context and simply in response to cache theft, then cache suppression should occur. In the current experiment, we found that the birds maintained caching throughout the experiment. We report that males increased caching in response to a manipulation in which caches were artificially added, suggesting the birds could adapt to the cooperative nature of the task. Additionally, we show that caching decisions were not solely due to motivational factors, instead showing an additional influence attributed to the behaviour of the partner bird.